The influence of heat treatment on the structure and microstructure of ti-15Mo-xNb system alloys for biomedical applications - Martins Jr, José Roberto Severino [UNESP]; Grandini, Carlos Roberto [UNESP] (My University, 2014)
The Ti-15Mo-xNb system integrates a new class of titanium alloys without the presence of aluminum and vanadium, which exhibit cytotoxicity, and that have low elasticity modulus values (below 100 GPa). This occurs because these alloys have a beta structure, which is very attractive for use as biomaterials. In addition, Brazil has about 90% of the world's resources of niobium, which is very important economically. It strategically invests in research on the development and processing of alloys containing this element. In this paper, a study of the influence of heat treatments on the structure and microstructure of the alloys of a Ti-15Mo-xNb system is presented. The results showed grain grown with heat treatment and elongated and irregular grains after lamination due to this processing. After quenching, there were no changes in the microstructure in relation to heattreated and laminated conditions. These results corroborate the x-ray diffraction results, which showed the predominance of the β phase. © (2014) Trans Tech Publications, Switzerland.
Keywords: Heat treatments; Microstrain; Microstructure; Ti alloys